Correction: Zhou et al. Notoginsenoside R1 Ameliorates Diabetic Retinopathy through PINK1-Dependent Activation of Mitophagy. Cells 2019, 8, 213 - Ping Zhou; Weijie Xie; Xiangbao Meng; Yadong Zhai; Xi Dong; Xuelian Zhang; Guibo Sun; Xiaobo Sun (Cells)
In the original publication [...]